Paleoneurologia de antifer (mammalia: cervidae), um cervídeo extinto da América do Sul - Machado, Emmanuelle Fontoura (2021)
Terrestrial Cetartiodactyla arose in North America and Europe during the early Eocene and diversified, giving rise, among others, to the clade Ruminantia, which includes Cervidae. Cervidae is divided into Cervinae, European and Asian deer, and Capreolinae, the American deer. The formation of the Isthmus of Panama (late Pliocene) enabled the biotic interchange between the continents of North and Central Americas, and South America (Great American Biotic Interchange), where the Cervidae radiated quickly after their arrival. Paleoneurology is a branch of paleontology that is dedicated to the study of neurological evolution through time. Using computed tomography techniques, it is possible to access the endocranial morphology of extinct species. Here, we studied the brain endocast of the extinct late Pleistocene cervid Antifer ensenadensis from southern Brazil, one of the largest forms that lived on this continent. Comparative morphology, geometric morphometrics, and encephalization quotients were employed to compare this extinct species with other American and Eurasian forms. For this purpose, specimens from the Touro Passo Formation (Upper Pleistocene), southern Brazil, were scanned, and virtual models of the endocranial cavity were generated. The analyzed endocasts demonstrate that A. ensenadensis had a gyrencephalic brain, showing a prominent longitudinal sinus (=sagittal superior sinus), which is also observed in the large South American cervid Blastocerus dichotomus. Also, the endocast is anteroposteriorly elongated and rhomboid in shape. The geometric morphometric analysis suggested a clear and linear allometric trend between brain endocast size and shape and highlights A. ensenadensis as an extreme form within the analyzed cervids regarding brain morphology. The encephalization coefficient of A. ensenadensis (0.68, Jerison, 1973; 0.63, Eisenberg, 1981) is within the range of extant cervids (0.64 - 1, Jerison, 1973; 0.60 - 1.06, Eisenberg, 1981) - suggesting that the pattern of encephalization of South American forms was already established at least since the end of the Pleistocene.